Implantable cardioverter defibrillator shocks from ventricular tachyarrhythmias in patients with ischemic heart disease: Preventative measures, shortcomings, cost‐effectiveness, and global practice perspectives. (19th July 2021) - Kantharia, Bharat K.
Abstract: Implantable cardioverter defibrillators (ICDs) have proven to be life‐saving devices in patients with ischemic cardiomyopathy (ICM) who are prone to develop ventricular tachycardia (VT) and fibrillation (VF). Antiarrhythmic drugs (AADs) are commonly prescribed in many such patients with ICDs to treat and prevent different forms of arrhythmias in clinical practice. When these patients experience recurrent monomorphic VT despite chronic AADs therapy, or when AAD therapy is contraindicated or not tolerated, and VT storm is refractory to AAD therapy, catheter ablation constitute guideline‐based class I indication of treatment. However, what should be the most appropriate strategy to prevent first ICD shock or subsequent multiple shocks from VT/VF in patients with ICM who undergo ICD implantation without prior incidence of cardiac arrest, remains debatable. The purpose of this review is to discuss preventative aspects of ICD shocks for VT and the shortcomings of these measures along with the cost‐effectiveness and global perspectives based on the current knowledge of the topic.